2014
DOI: 10.4081/cp.2014.647
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Hemoptysis Caused by Hughes-Stovin Syndrome

Abstract: Hughes and Stovin first reported a syndrome consisting of multiple pulmonary artery aneurysms and venous thrombosis in 1959. Here, we encountered a 42-year old woman who had hemoptysis revealing a Hughes-Stovin syndrome. Helical computed tomography showed multiple pulmonary artery aneurysms with pulmonary thromboembolism. The patient was treated with steroid therapy, cyclophosphamide and anticoagulation with a good response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The reported cases ranged between 12 to 48 years of age [5,6] but Korunic et al reported a 70-year-old male patient with HSS [7]. Only seven women have been reported presenting this syndrome thus far [8]. The exact etiology and pathogenesis of HSS remains widely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported cases ranged between 12 to 48 years of age [5,6] but Korunic et al reported a 70-year-old male patient with HSS [7]. Only seven women have been reported presenting this syndrome thus far [8]. The exact etiology and pathogenesis of HSS remains widely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Chest radiography may reveal round opacities and hilar enlargement. Helical computed tomography (HCT) and magnetic resonance imaging have been reported as non-invasive method useful for the diagnosis of PAA [8]. Traditionally, conventional angiography has been regarded as a gold standard for the diagnosis of pulmonary artery aneurysms [2].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Typically young men between the second and fourth decades are affected. [4][5][6][7] The prevalence of the disease worldwide is less than 1:1,000,000, [4] making it extremely rare. The clinical symptoms are recurrent fever, chills, peripheral venous thrombosis, multiple pulmonary artery aneurysms, cough, fatigue, dyspnea, chest pain and hemoptysis.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical symptoms are recurrent fever, chills, peripheral venous thrombosis, multiple pulmonary artery aneurysms, cough, fatigue, dyspnea, chest pain and hemoptysis. [5][6][7] Further, nearly all patients with Behçet's disease present oral mucocutaneous ulcerations in the form of aphthous ulcers. Additionally, patients may present with genital ulcers, erythema nodosum, cutaneous pustular vasculitis or uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Hughes-Stovin syndrome is a rare condition, characterized by the combination of multiple pulmonary artery aneurysms and peripheral venous thrombosis, that mainly affects males (80-90% of cases) between the second and fourth decades of life ( 7 - 11 ) . Although the lesions often affect arteries and veins simultaneously (in 68% of cases), isolated arterial or venous impairments are reported at frequencies of 25% and 7%, respectively ( 9 , 11 ) .…”
mentioning
confidence: 99%